Psb28 protein is involved in the biogenesis of the photosystem II inner antenna CP47 (PsbB) in the cyanobacterium Synechocystis sp. PCC 6803 - Dobáková, Marika; Sobotka, Roman; Tichý, Martin; Komenda, Josef (Plant physiology, 2009)
The role of the Psb28 protein in the structure and function of the photosystem II (PSII) complex has been studied in the cyanobacterium Synechocystis sp. PCC 6803. The protein was localized in the membrane fraction and, whereas most of the protein was detected as an unassembled protein, a small portion was found in the PSII core complex lacking the CP43 antenna (RC47). The association of Psb28 with RC47 was further confirmed by preferential isolation of RC47 from the strain containing a histidine-tagged derivative of Psb28 using nickel-affinity chromatography. However, the affinity-purified fraction also contained a small amount of the unassembled PSII inner antenna CP47 bound to Psb28-histidine, indicating a structural relationship between Psb28 and CP47. A psb28 deletion mutant exhibited slower autotrophic growth than wild type, although the absence of Psb28 did not affect the functional properties of PSII. The mutant showed accelerated turnover of the D1 protein, faster PSII repair, and a decrease in the cellular content of PSI. Radioactive labeling revealed a limitation in the synthesis of both CP47 and the PSI subunits PsaA/PsaB in the absence of Psb28. The mutant cells contained a high level of magnesium protoporphyrin IX methylester, a decreased level of protochlorophyllide, and released large quantities of protoporphyrin IX into the medium, indicating inhibition of chlorophyll (Chl) biosynthesis at the cyclization step yielding the isocyclic ring E. Overall, our results show the importance of Psb28 for synthesis of Chls and/or apoproteins of Chl-binding proteins CP47 and PsaA/PsaB.
Keywords: bakteriální proteiny; Photosystem II Protein Complex; delece genu; Synechocystis; Light-Harvesting Protein Complexes; Mutation; mutace; světlosběrné proteinové komplexy; Bacterial Proteins; Gene Deletion; fotosystém II (proteinový komplex)